A Novel Leptospira interrogans Protein LIC13086 Inhibits Fibrin Clot Formation and Interacts With Host Components - Passalia, Felipe José; Heinemann, Marcos Bryan; Vieira, Mônica Larucci; Nascimento, Ana Lucia T. O. (Frontiers in Cellular and Infection Microbiology, 2021)
Leptospirosis is a neglected zoonosis, caused by pathogenic spirochetes bacteria of the genus Leptospira. The molecular mechanisms of leptospirosis infection are complex, and it is becoming clear that leptospires express several functionally redundant proteins to invade, disseminate, and escape the host’s immune response. Here, we describe a novel leptospiral protein encoded by the gene LIC13086 as an outer membrane protein. The recombinant protein LIC13086 can interact with the extracellular matrix component laminin and bind plasminogen, thus possibly participating during the adhesion process and dissemination. Also, by interacting with fibrinogen and plasma fibronectin, the protein LIC13086 probably has an inhibitory effect in the fibrin clot formation during the infection process. The newly characterized protein can also bind molecules of the complement system and the regulator C4BP and, thus, might have a role in the evasion mechanism of Leptospira. Taken together, our results suggest that the protein LIC13086 may have a multifunctional role in leptospiral pathogenesis, participating in host invasion, dissemination, and immune evasion processes.